Evaluation of hospital pharmacy services: an integrative review - Rodrigo Fonseca Lima (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Background: Pharmaceutical services performed in the hospital context have specific structure and processes, which should be continuously evaluated because they influence the results obtained.